China, its history, arts, and literature - Brinkley, Captain F. (J. B. Millet Co., 1902)
This book introduce about Chinese porcelain and pottery, early wares of China. Wares of the "Sung" (960 - 1279) dynasty. Sung and Yuan wares, porcelain decorated under the glaze. Porcelain decorated over the glaze. Monochromatic glazes.